274 From Clinical Care Programme to Frailty Pathway; a Multidisciplinary, Interagency Journey. (16th September 2019) - Casey, Amanda; Wei Fan, Chie; Duggan, Joseph
Abstract: Background: The National Clinical Programme for Older Persons was introduced in the Model 4 Adult teaching hospital in 2012 with the development of a Specialist Geriatric Ward, supported by an existing Day Hospital and access to post acute rehabilitation in the local model 3 hospital. The continuing growth of the population over 70 years in the catchment area and the increasing awareness of the complex needs of this group of patients required a new way of thinking and working. Methods: Using Lean methodology the group restructured the focus of the care pathway for older persons using evidence based practice and data collection. Workstreams have been identified and iterative project charters established to guide and empower staff to design and evaluate the supports they provide. Key internal and external stakeholders were identified and invited to participate in the ongoing steering group and the voice of the customer was used to underpin targeted improvements. Results: The hospital now has a structured framework for the delivery and evaluation of care provided to older persons attending our services. Overall governance is provided by a Frailty Steering Group with strong clinical leadership and is informed by agreed quality indicators and realtime data. Despite increases in numbers requiring admission, length of stay has decreased, readmission rates have remained stable and a greater proportion of our patients are accessing both offsite rehabilitation and home supports on discharge. Conclusion: This is an ongoing project with medium and long term goals identified across all workstreams. The evidence and data gathered will inform service planning and resource allocation. A number of collaborative research proposals are now being considered from across acute hospital and Community Healthcare Organisation.